Experimental analysis of multi-component intervention to support youth in integrated work settings. - Mazzotti, Valerie L.; Kittelman, Angus; Bromley, Katherine W.; Hirano, Kara A. (Journal of Vocational Rehabilitation, 2020)
BACKGROUND: Work-based learning experiences provide secondary students meaningful opportunities to acquire skills needed for long-term employment. Students with disabilities engaging in problem behaviors on the job are vulnerable to having employment opportunities reduced or terminated. One way to develop appropriate work-based behaviors that may promote long-term, competitive integrated employment is to address problem behaviors in high school to ensure students enter the workforce career ready. OBJECTIVE: The purpose of this study was to examine the effects of a function-based, self-determined multi-component intervention on the reduction of work-based problem behaviors for secondary youth with disabilities. METHODS: This study used a single-case A-B-A-B withdrawal design to examine the effects of the intervention on two student participants' off-task, work-based problem behaviors. RESULTS: Based on visual analysis of graphed data, results indicated a functional relation between the function-based, self-determined multi-component intervention and decrease in off-task, work-based problem behaviors for each student participant. The intervention was rated as socially valid by students and job coaches. CONCLUSIONS: This study provides empirical evidence to support implementation of using FBAs and self-determination interventions in combination during work-based learning experiences to decrease work-based problem behaviors for secondary students with disabilities. Limitations and implications for future research and practice are discussed.